2012
DOI: 10.1038/nmat3454
|View full text |Cite
|
Sign up to set email alerts
|

Singular characteristics and unique chemical bond activation mechanisms of photocatalytic reactions on plasmonic nanostructures

Abstract: The field of heterogeneous photocatalysis has almost exclusively focused on semiconductor photocatalysts. Herein, we show that plasmonic metallic nanostructures represent a new family of photocatalysts. We demonstrate that these photocatalysts exhibit fundamentally different behaviour compared with semiconductors. First, we show that photocatalytic reaction rates on excited plasmonic metallic nanostructures exhibit a super-linear power law dependence on light intensity (rate ∝ intensity(n), with n > 1), at sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

34
909
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 785 publications
(947 citation statements)
references
References 48 publications
34
909
1
3
Order By: Relevance
“…The average lifetime of the vibrationally excited states of adsorbates on metals corresponds to~10 −12 -10 −11 s. Linear-to-superlinear regime transition takes place for electron scattering events occurring at rates of 10 11 -10 12 s −1 or higher [13,31]. For instance, the rate of plasmonic ethylene epoxidation on Ag nanocubes exhibits linear dependence on intensity up to 300 mW cm −2 and a superlinear dependence above 300 mW cm −2 ( Figure 6C) [124]. The kinetic isotope effect, the second experimental signature of electron-driven reactions, is defined as the ratio between the rates of a reaction involving a light isotope with respect to the same reaction with a heavier one.…”
Section: Direct Plasmonic Photocatalysismentioning
confidence: 98%
See 1 more Smart Citation
“…The average lifetime of the vibrationally excited states of adsorbates on metals corresponds to~10 −12 -10 −11 s. Linear-to-superlinear regime transition takes place for electron scattering events occurring at rates of 10 11 -10 12 s −1 or higher [13,31]. For instance, the rate of plasmonic ethylene epoxidation on Ag nanocubes exhibits linear dependence on intensity up to 300 mW cm −2 and a superlinear dependence above 300 mW cm −2 ( Figure 6C) [124]. The kinetic isotope effect, the second experimental signature of electron-driven reactions, is defined as the ratio between the rates of a reaction involving a light isotope with respect to the same reaction with a heavier one.…”
Section: Direct Plasmonic Photocatalysismentioning
confidence: 98%
“…This opens the possibility to manipulate and control the reaction selectivity. Electron-driven reactions can be distinguished from phonon-driven processes due to (a) transition from linear to superlinear dependence of the reaction rate on the incident photon flux [13,31,124], and (b) higher kinetic isotope effect [31,125]. In metals, the rate of charge carrier formation is linearly dependent on the photon flux.…”
Section: Direct Plasmonic Photocatalysismentioning
confidence: 99%
“…The high catalytic activity of the MoS 2 nanoparticles has been directly linked to the presence of metallic edge states on the otherwise semiconducting MoS 2 nanoparticles [21]. Very recently, an observed extraordinary photocatalytic behavior of metallic nanoparticles has been shown to originate from the excitation * kiran@fysik.dtu.dk of LSPRs [22,23]. As we predict here, the metallic edge states on MoS 2 nanostructures can lead to the formation of highly localized 1D plasmons-a result that adds edge plasmonics to the list of this material's unique properties with potential applications within nanoplasmonics and photocatalysis.…”
mentioning
confidence: 99%
“…Conventional photocatalysts are almost exclusively focused on the study of inorganic semiconductor materials such as TiO 2 , [9][10][11][12][13][14] however, poor light absorption and the fast electron/hole recombination [15] limited the use of these photocatalysts. To overcome these problems, great efforts have recently been devoted to using plasmonic metallic nanostructures in the field of photocatalysis [16][17][18][19][20][21] due to their surface plasmon resonance property [22,23] which is beneficial for light absorption and increase of photogenerated charge carriers energy intensity under visible light irradiation. Dong et al found that Bi nanostructure exhibited a remarkable and stable photocatalytic activity due to its surface plasmon resonance.…”
Section: Introductionmentioning
confidence: 99%